Enzymatic esterification of glycerol and stearic acid in non-conventional media - Csanádi, Zsófia; Bélafi-Bakó, Katalin; Szentgyörgyi, Eszter; Gubicza, László; Knez, Željko; Leitgeb, Maja (Slovensko kemijsko društvo, 2015)
Ionic liquids as trihexyl-tetradecyl-phophonium-dicyanamide (Cyphos 105) and cocosalkyl-pentaethoxi-methyl-ammonium-methosulfate (Ammoeng 100) were applied for the esterification of stearic acid and glycerol using Candida antarctica lipase (Novozyme 435). When only ILs were applied as solvents at 1:15 initial substrate molar ratio the conversion was 76 and 78 % in the case of two kinds of ILs, respectively. Mixed the ILs and supercritical $CO_2$ the conversion reached 79 and 86 %. The conversion was found highest in supercritical $CO_2$, reached 90 %. Moreover formation of glycerol-di-stearate is much lower in the case of ILs comparing with $SCCO_2$. Ionski tekočini (ILs) triheksil-tetradecil-fofonijev-dicianamid (Cyphos 105) in kokosalkil-pentaetoksi-metil-amonijev-metosulfat (Ammoeng 100) smo uporabili kot topili pri reakciji esterifikacije stearinske kisline in glicerola z lipazo iz Candida antarctice (Novozyme 435). Pri začetni množinski koncentraciji substrata 1:15 in v primeru, ko smo uporabili ILs kot samostojni topili, je bila dosežena presnova 76 in 78 %. Višjo, 90 % presnovo smo dosegli v superkritičnem $CO_2$. V primeru uporabe ILs je nastalo več glicerol distearata kot v primeru uporabe $ScCO_2$.